Meningkatkan Hasil Belajar Volume Balok dengan Model Pembelajaran PBL serta NHT - Candra; Sunarno (CV. ITTC INDONESIA, 2024)
This study aims improve student learning outcomes PBL and NHT models in grade V SDN Lok Rawa Barito Kuala, this study involved 14 students. This study uses Classroom Action Research Technique which qualitative approach for two cycles. The information used qualitative information measurable observation of student and teacher participation in educational activities, information form of learning outcomes obtained by individual written tests end cycle. According to the results study, teacher activity scored 21 with the